Future oriented conservation: knowledge governance, uncertainty and le arning - Wyborn, Carina; Kerkhoff, Lorrae; Dunlop, Michael; Dudley, Nigel; Guevara, Oscar (Biodiversity and Conservation)
Despite significant progress in understanding climate risks, adaptatio n efforts in biodiversity conservation remain limited. Adaptation requ ires addressing immediate conservation threats while also attending to long term, highly uncertain and potentially transformative future cha nges. To date, conservation research has focused more on projecting cl imate impacts and identifying possible strategies, rather than underst anding how governance enables or constrains adaptation actions. We out line an approach to futureoriented conservation that combines the capa cities to anticipate future ecological change; to understand the impli cations of that change for social, political and ecological values; an d the ability to engage with the governance (and politics) of adaptati on. Our approach builds on the adaptive management and governance lite rature, however we explicitly address the (often contested) rules, kno wledge and values that enable or constrain adaptation. We call for a b roader focus that extends beyond technical approaches to acknowledge t he sociopolitical challenges inherent to adaptation. More importantly, we suggest that conservation policy makers and practitioners can use this approach to facilitate learning and adaptation in the context of complexity, transformational change and uncertainty.